(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the problems related to the quality of education in the process of integrating digital technologies into modern education systems. Digital technologies play a significant role in making education more interactive and effective. However, the implementation of these technologies faces some obstacles, including the provision of digital competencies for teachers, inadequate technological infrastructure, and challenges in effective integration. The article explores ways to overcome these problems.